ARGUMENTASI SUNNAH DAN SYI’AH TENTANG HUKUM PERNIKAHAN MUT’AH (KAJIAN KRITIS METODOLOGIS) - chamim tohari (Hukum Islam, 2020)
This research examines about mut'ah marriage law and its argumentations, both from the Sunnah and Shi'a groups. This study is limited to the following problem formulations: (1) How is the law of marriage mut'ah according to the Sunnah group and its argumentations? (2) What is the law of mut'ah marriage according to the Shi'ites and their argumentation? (3) What are the similarities and differences in the manhaj used between the Sunnah and Shiite groups related to the mut'ah marriage law? And (4) And (4) How strong are the sources of law and manhaj that are used to determine mut'ah marriage law? This research is a library research (library research) with ushuliyah approach as the approach chosen to understand and conclude this problem. The results of this study can be concluded that according to the Sunnah schools of thought, mut'ah marriage is haram forever, while according to the Shi'ite schools of mut'ah is lawful for eternity. This difference is not only due to the difference in the use of an exploitative argument, it is also caused by differences in manhaj in punishing mut'ah marriages. The similarity is that the two groups use the Qur'anic proposition, but differ in interpretation. Both groups also use the Hadith argument, but it is exploitative. The Sunnah group in their ijtihad uses the nasakh-mansukh, qiyas and istislahi methods, while the Shi'a group uses the tarjih, ijma 'sahabah, istishab and istislahi methods. According to the author, the arguments and arguments of the two groups together do not reach a convincing degree (qath'i). So the authors suggest that what should be used to forbid or justify mut'ah is the argument of limitation and maslahah.